The Influence of the Theory of Planned Behavior (TPB) and Service Quality on Public Interest in Using BSI in Pematang Siantar - azzahri, khairul; Maidalena, Maidalena; Syarvina, Wahyu (UNIVERSITAS PAKUAN, 2025)
This study aims to evaluate the influence of Theory of Planned Behavior (TPB) and service quality on public interest in using Bank Syariah Indonesia (BSI) services in Pematang Siantar City. This study adopted a quantitative method with primary data collected through a field survey of 30 selected respondents using purposive sampling technique. Data analysis was carried out by multiple linear regression using SPSS version 26 software. The results showed that partially, both TPB and service quality have a significant impact on people's interest in using BSI. In addition, simultaneously, the two variables also contribute significantly in influencing customer interest. The coefficient of determination (R²) value of 42.8% indicates that TPB and service quality are able to explain most of the variation in people's interest, while the rest is influenced by other factors not included in this research model. This study confirms that factors such as behavioral attitudes, subjective norms, perceived behavioral control, as well as service quality dimensions such as tangibles, reliability, responsiveness, assurance, and empathy play an important role in the community's decision-making process to use Islamic banking services. The practical implications of these findings emphasize the importance of increasing education and promotion of Islamic banking principles and products to the wider community. BSI is advised to continue to innovate in service aspects and strengthen the elements of SDGs in order to increase public interest, especially in potential areas such as Pematang Siantar.